Financial inequality: The relationship between consumer taxes and social programs in the Argentine Republic in the period 2015-2019 - Rezzoagli, Luciano Carlos (2021)
Despite the implementation of several Conditional Money Transfer Programs (CMT) and the consequent reduction in poverty and indigence rates, without ignoring that said reduction has been controversial due to its low level of evaluation and control; as well as the effective increment in job placement of vulnerable population sectors, Argentina keeps having high levels of inequality. From a financial analysis aspect, this situation is largely due to the consolidation of a highly regressive detractive system, characterized by the imposition of indirect taxes that are levied on productive and intermediate activities and final consumer products without taking into account the effective tax capacity of the actual or incidental recipients of the tax. In a country like Argentina, which belongs to the most unequal continent in the world, it is essential to start being, and not seem; by this, we mean that the fiscal system structure must pursue and encourage the achievement of a structural middle class, starting by having in consideration the severe economic asymmetries, which occur both at a population level as well at a regional geographic context. One of the main situations that countless families suffer is the lack of coordination of fiscal reforms that tend to the development and consolidation of a structural middle class through a progressive, inclusive and liable tax system.